EFEKTIVITAS ICE MASSAGE TERHADAP PENURUNAN NYERI LOW BACK PAIN PADA ANAKLow Back Pain is the movement of the back muscles will cause pain at the same time will increase the muscle spasm that limits the range space of motion of the lower back. Pain treatme - Potabuga, Isra Nur Utari Syachnara Potabuga (Politeknik Kesehatan Kemenkes Sorong, 2023)
Low Back Pain is the movement of the back muscles will cause pain at the same time will increase the muscle spasm that limits the range space of motion of the lower back. Pain treatment can be overcome by using non-pharmacological therapy, namely by using ice massage. The purpose of this study was to viewing the effectiveness of giving ice massage to reduce low back pain on children. The research method used is a quasi-experimental design with Non–equivalen control group with pre test and post test, the sample used is 30 children. The sampling technique uses non-probability sampling, namely purposive sampling which is based on certain considerations made by the researcher himself. The results showed that there was an effect that ice massage was effective to reduce low back pain on children with p value = 0.000 (p value 0.05). Ice massage can cause a closing mechanism for pain impulses when gently rubbing the back.